Do needs motivate the exchange of data in transboundary waters? Insights from Africa’s shared basins - Mukuyu, Patience; Lautze, Jonathan F.; Rieu-Clarke, A.; Saruchera, D.; McCartney, Matthew P. (Informa UK Limited, 2023)
Despite widespread recognition of the importance of data exchange in transboundary waters’ management, there is growing evidence that data exchange is falling short in practice. A possible explanation may be that data exchange occurs where and when it is needed. Needs for data exchange in shared waters, nonetheless, have not been systematically assessed. This paper evaluates data exchange needs in a set of transboundary basins and compares such needs with evidenced levels of data exchange. Our findings indicate that it may be possible to accelerate data exchange by identifying and promoting the exchange of data that respond to palpable need and serve practical use.